AN EVALUATION OF SAFETY RISK FACTORS DURING INSTALLATION AND DISMANTLING OF TOWER CRANES IN CONSTRUCTION SITES (Nigerian Journal of Technology, 2020)
The construction industry plays a central and significant role in the economy of any nation. One of the major reasons for ineffective project delivery in the Nigerian construction industry is the improper assessment of risk factors. The industry however is currently facing a lot of challenges which include constant increase in the rate of accidents on construction sites which could be due to ineffective safety management as construction companies are usually interested in maximizing their profit in order to secure funds for new investments, and cover possible expenses associated with the occurrence of risk factors during construction. Installation and dismantling of tower crane had been previously looked at as a general safety issue until, recent research showed that about 69% of accidents related to tower cranes in Korea from 2001-2011, occur during installation and dismantling process. In view of this, this paper aimed at evaluating safety risk factors during installation and dismantling by determining their probability of occurrence and degree of impact with a view to establishing the most significant ones. This is why a well-structured questionnaire was designed to collect data with respect to their probability of occurrence and degree of impact using a 5 point Likert scale. Responses from the administered questionnaire and interactions were collated, interpreted and analysed using descriptive statistics (mean) and results presented in tables. Results showed that abrasion (wear and tear of components such as bolts, nuts, or pins) is the most probable factor with a mean value of 3.63. Fracture of a wire rope during dismantling had the highest degree of impact with a mean value of 4.63. The research concluded that fracture of a wire rope during dismantling and abrasion (wear and tear of components such as bolts, nuts, or pins) are highly affecting factor on safety during installation and dismantling. Adoption of a preventive maintenance strategy or routine check on the tower crane parts and components could help minimize the probability of occurrence and impact of the safety risk factors on site. http://dx.doi.org/10.4314/njt.v39i4.4